The long-term effects of take-overs on the South African economy - N. Bhana (South African Journal of Business Management, 1984)
Acquiring companies prefer growth through acquisitions and mergers rather than growth by direct investment in manufacturing resources. A justification for the large number of take-overs is the belief that abnormal gains are to be obtained so. There is substantial empirical evidence showing this untrue. Take-overs contribute immediate short-term gains, and are preferred to internal expansion where the benefits accrue over the long-term. Managers are usually evaluated on short-term performance criteria and therefore they have a bias for take-overs. Several investigators have studied the decline of the United States economy and the corresponding rise of Japan as industrial leader. The unrestrained take-over activity has been the chief reason for the decline of many industries in the United States. Acquiring companies have contributed to their own downfall by not investing sufficiently in up-to-date manufacturing resources. Take-overs lead to economic decline caused by lower productivity of acquired resources. South African companies are showing a strong preference for growth through take-overs. With the take-over process many local industries have come under the control of a few large conglomerates. South African acquiring companies could benefit by following the Japanese example of direct investments in technologically up-to-date manufacturing resources. More direct investment in manufacturing resources will lead to a more vigorous free-enterprise system and will raise the productivity of local industries. A more stringent Competition Act is necessary if South Africa is to avoid the harm to the economy caused by unrestrained take-over activity.
Keywords: 650